Pendekatan Pembelajaran Mendalam sebagai Strategi Inovatif dalam Pengajaran Bahasa Indonesia di Sekolah Dasar - Habibi Musa (Jurnal Pendidikan, Kepelatihan, Olahraga, dan Kesehatan, 2025)
Learning Indonesian in elementary schools plays a strategic role in developing students' basic literacy skills, including reading, writing, listening, and speaking. However, surface-based learning practices often lead students to focus solely on memorization without in-depth understanding. This literature review aims to analyze the concept, implementation, and impact of the deep learning approach in teaching Indonesian in elementary schools. The method used is a descriptive literature review, reviewing various relevant national and international research findings from 2019–2024. The study results indicate that the deep learning approach emphasizes the development of conceptual understanding, critical thinking skills, and reflective skills through meaningful and contextual learning activities. Implementing this strategy in Indonesian language learning has been proven to improve students' literacy skills, build intrinsic motivation, and strengthen connections between language and real-life experiences. Thus, the deep learning approach is a relevant innovative strategy for 21st-century education to improve the quality of Indonesian language learning in elementary schools.